2019
DOI: 10.1093/omcr/omy111
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of ‘saturation gap’: a case of dapsone-induced methaemoglobinemia in a pregnant mother with leprosy

Abstract: Limited data regarding methemoglobinemia in pregnancy, particularly secondary to dapsone is available up to date. We report a case of dapsone-induced methemoglobinemia in a pregnant mother with multibacillary leprosy who presented with fever, productive cough and cyanosis of 2 days duration 2 weeks after multidrug therapy was commenced. On examination, she had central cyanosis with low oxygen saturation (SpO2 = 84–88%). Arterial blood gas analysis showed PO2 of 111 mmHg and SO2 of 98 mmHg. Patient was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“… 19 22 It has been reported that methemoglobinemia can cause a discrepancy between the values of measured by a conventional pulse oximeter and the actual arterial oxygen saturation ( ) calculated by arterial blood gas measurement. 19 22 The values of are not proportional to the actual during methemoglobinemia, since elevated methemoglobin levels (up to 60%) force the value to be around 85%, whereas reaches . 19 When methemoglobin is elevated, the values measured by conventional pulse oximetry are inaccurate and can falsely diagnose the actual status of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 22 It has been reported that methemoglobinemia can cause a discrepancy between the values of measured by a conventional pulse oximeter and the actual arterial oxygen saturation ( ) calculated by arterial blood gas measurement. 19 22 The values of are not proportional to the actual during methemoglobinemia, since elevated methemoglobin levels (up to 60%) force the value to be around 85%, whereas reaches . 19 When methemoglobin is elevated, the values measured by conventional pulse oximetry are inaccurate and can falsely diagnose the actual status of patients.…”
Section: Resultsmentioning
confidence: 99%
“… 19 However, when the level of methemoglobin is high, the result is unreliable, because the pulse oximeter readings remain stable. 19 22 CO-oximetry is a bench-top analysis method for the evaluation of methemoglobin, and it has been used as the traditional detection tool for methemoglobinemia. Although CO-oximetry can be used to monitor the response to treatment for methemoglobinemia, it is costly and requires an invasive procedure for collecting blood samples from patients.…”
Section: Introductionmentioning
confidence: 99%
“…Methemoglobin is an aberrant form of hemoglobin arising from oxidation of heme iron to the ferric (Fe 3+ ) form, resulting in a left shift in the oxygen saturation curve [ 1 ]. Hemolytic anemia may follow drug-induced methemoglobinemia, especially with exposure to dapsone and sulfonamides [ 2 ]. Clinicians should have a high index of suspicion and be able to recognize methemoglobinemia as an adverse effect attributable to dapsone use, particularly when patients present with cyanosis and hypoxemia of unclear etiology and there is a saturation gap (ie, a difference between oxygen saturation measured by pulse oximetry and arterial blood gas analysis) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemolytic anemia may follow drug-induced methemoglobinemia, especially with exposure to dapsone and sulfonamides [ 2 ]. Clinicians should have a high index of suspicion and be able to recognize methemoglobinemia as an adverse effect attributable to dapsone use, particularly when patients present with cyanosis and hypoxemia of unclear etiology and there is a saturation gap (ie, a difference between oxygen saturation measured by pulse oximetry and arterial blood gas analysis) [ 2 ]. Our patient demonstrated oxygen-resistant cyanosis with a saturation gap of 37%.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal level of methemoglobin (methemoglobinemia) may result from congenital enzyme deficiencies [9,19] or exposure to certain chemicals and medications turning hemoglobin into a dysfunctional form of hemoglobin [20][21][22][23][24]. These chemical agents include drugs used in hospitals and health care settings, such as some local anesthetics (e.g., benzocaine and lidocaine [20][21][22]) and antibiotics (e.g., dapsone [23]), as well as nitrates and nitrites present in fertilizers that may contaminate food and water supplies [24,25]. The initial symptoms appear as a bluish discoloration of the skin when the methemoglobin level is at least 10-20% of the total hemoglobin .…”
Section: Introductionmentioning
confidence: 99%